2015
DOI: 10.1038/ncomms8433
|View full text |Cite|
|
Sign up to set email alerts
|

Cidea improves the metabolic profile through expansion of adipose tissue

Abstract: In humans, Cidea (cell death-inducing DNA fragmentation factor alpha-like effector A) is highly but variably expressed in white fat, and expression correlates with metabolic health. Here we generate transgenic mice expressing human Cidea in adipose tissues (aP2-hCidea mice) and show that Cidea is mechanistically associated with a robust increase in adipose tissue expandability. Under humanized conditions (thermoneutrality, mature age and prolonged exposure to high-fat diet), aP2-hCidea mice develop a much more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 58 publications
7
81
0
Order By: Relevance
“…Cold stress increases catecholamine levels, thereby activating nonshivering thermogenesis in BAT and substantially increasing food intake and metabolic rate [22]. Thus, it has been informative to characterize mouse models with genetic alterations in energy storage at room temperature (23 °C) versus thermoneutrality (30 °C), a temperature that poses no thermal stress and little BAT activation [23], [34], [35]. Recently, it has been demonstrated that housing mice with LD protein deficiencies at thermoneutrality reveals phenotypes that more closely resemble lipodystrophic syndromes in humans with mutations in LD protein genes [36].…”
Section: Resultsmentioning
confidence: 99%
“…Cold stress increases catecholamine levels, thereby activating nonshivering thermogenesis in BAT and substantially increasing food intake and metabolic rate [22]. Thus, it has been informative to characterize mouse models with genetic alterations in energy storage at room temperature (23 °C) versus thermoneutrality (30 °C), a temperature that poses no thermal stress and little BAT activation [23], [34], [35]. Recently, it has been demonstrated that housing mice with LD protein deficiencies at thermoneutrality reveals phenotypes that more closely resemble lipodystrophic syndromes in humans with mutations in LD protein genes [36].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, overexpression of glucose transporter GLUT4 (Shepherd et al, 1993) or mitochondrial protein mitoNEET (Kusminski et al, 2012) in WAT, with the consequent increase in fat mass, has been shown to enhance insulin sensitivity. In turn, increased adipose tissue expandability also resulted in an improved metabolic profile under a high-fat diet (Abreu-Vieira et al, 2015). On the other hand, blockage of adipose tissue expandability is associated with severe metabolic alterations (Medina-Gomez et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…and were transferred to metabolic chambers as previously described [54]. The mice were measured at 33 °C to obtain basal values during 10 min.…”
Section: Methodsmentioning
confidence: 99%